Web-Based Application to Support Physical Fitness Information of Elderly People - Dharmawan, Yudhy; Suroto, Suroto; Putra, Priguna Septia (UI Scholars Hub, 2018)
Penduduk lanjut usia (lansia) semakin banyak seiring meningkatnya usia harapan hidup. Banyak upaya yang harus dilakukan untuk mencegah kesakitan di lansia, salah satunya dari aspek preventif dengan menjaga kebugaran para lansia. Untuk memonitor status kebugaran lansia, maka diperlukan aplikasi pemantauan kebugaran jasmani berbasis teknologi web karena tidak ada sistem yang merekam data kebugaran para lansia. Aplikasi ini ditujukan untuk merekam data kebugaran jasmani para lansia untuk merekomendasikan gym yang sesuai berdasarkan kondisi kesehatan yang dapat diakses di mana saja. Aplikasi ini dibuat dengan bahasa pemrograman PHP dan MYSQL sebagai pengolahan basis data yang dilengkapi dengan grafik untuk memantau kebugaran jasmaninya. Hasil uji menunjukkan bahwa aplikasi mampu berfungsi dengan baik yang ditunjukkan dengan berfungsinya seluruh menu yang didesain dan dikembangkan. Sistem mampu merekam data individu serta kebugaran lansia. Sistem mampu menyajikan informasi dan riwayat kebugaran lansia serta rekomendasi latihan kebugaran yang sesuai. The number of elderly people is more increasing along with the rising of the life expectancy age. There are many efforts that should be carried out to prevent the elderly, one of which from the preventive aspect is by maintaining the physical fitness of the elderly. To monitor the fitness status of the elderly, it needs an application of the web technology-based physical fitness monitoring because has been no system that records elderly fitness data. This application was to record physical fitness data of the elderly to recommend the appropriate gym based on the health condition which can be accessed anywhere. This application was made with the PHP and MYQSL program language as the database processing equipped by the graphic to monitor the physical fitness. The results of the test showed that the application worked properly. As indicated by the functioning of the designed and developed menues. The system was able to record the individual data and the physical fitness of the elderly, also able to serve the information and the records of the fitness of the elderly people and the appropriate recommendation on fitness exercise.